2014
DOI: 10.1002/jtr.2025
|View full text |Cite
|
Sign up to set email alerts
|

Employee Turnover Intention in Travel Agencies: Analysis of Controllable and Uncontrollable Factors

Abstract: High turnover rates have long been a problem and costly in many industries. Numerous studies have focused on the reasons for employee turnover; however, most have focused on the hospitality industry but scarce in travel agencies. Thus, this research aimed to examine the situation in travel agencies in Hong Kong. A sample of 200 frontline staff was selected by convenience sampling. The results indicated that five independent variables, namely, general job satisfaction, job hopping, job security, training opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
0
29
1
Order By: Relevance
“…Today, one of the significant challenges in the service‐providing industries, especially tourism industry, to reach high levels of productivity, efficiency, and quality of services for customers is the decision of employees to stay or quit (Kim, ; Pang, Kucukusta, & Chan, ). As such, the literature reports the highest rate of quitting in the tourism industry, particularly among the female employees due to factors such as work overload and irregular working hours (Lin, Wong, & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, one of the significant challenges in the service‐providing industries, especially tourism industry, to reach high levels of productivity, efficiency, and quality of services for customers is the decision of employees to stay or quit (Kim, ; Pang, Kucukusta, & Chan, ). As such, the literature reports the highest rate of quitting in the tourism industry, particularly among the female employees due to factors such as work overload and irregular working hours (Lin, Wong, & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the statements "I feel emotionally drained from work" and "I feel I am working too hard on my job" showed the most remarkable variation between hotels and travel agencies employees. On the other hand, Pang, Kucukusta, and Chan's (2015) study found that travel agencies' work environment entails dealing with many systems, paperwork requirements and duties that staff would not encounter in other jobs, with which entry-level frontline staff would be required to become familiar. Accordingly, working in travel agencies involves high job pressure and a higher level of turnover.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to their isolated work environments (Fu, 2016). In his study on Hong Kong travel agencies, Pang et al (2015) found that supervisor support did not play a role in changing work climate for frontline employees. It is assumed that individual consideration that supervisors demonstrate toward their subordinates, as well as, the extent to which they provide coaching can help them to better fulfill their job responsibilities (Rafaeli et al, 2012;Han et al, 2016).…”
Section: The Moderating Role Of Perceived Supervisor Support 297mentioning
confidence: 96%
“…In the literature, there are few studies addressing the concepts of employees' advocacy and job embeddedness. The empirical studies found out a significant association between: employees' advocacy and their turnover intention (Akgü ndü z and Sanli, 2017; Yeh, 2014;Pang et al, 2015); job embeddedness and intentions to leave (Akgü ndü z and Cin, 2015; Peltokorpi et al, 2017); and employees' advocacy and job embeddedness (Akgü ndü z and Cin, 2015). In addition, the turnover intention of employees has been found to be negatively influenced by the employees' advocacy (Yeh, 2014;Singh and Sharma, 2016) and job embeddedness (Crossley et al, 2007;Robinson et al, 2014).…”
Section: Supervisors Support Job Embeddedness and Organisational Commentioning
confidence: 99%